PLGA Nanospheres as Delivery Platforms for Eimeria mitis 1a Protein: A Novel Strategy to Improve Specific Immunity - Xu, Lixin; Yu, Zhengqing; He, Ke; Wen, Zhaohai; Aleem, Muhammad Tahir; Yan, Ruofeng; Song, Xiaokai; Lu, Mingmin; Li, XiangRui (Frontiers in Immunology, 2022)
The infections of chicken coccidiosis impact the welfare of chickens and the economical production of poultry. Eimeria mitis is ubiquitous in chicken coccidiosis, and E. mitis infection can significantly affect the productivity of birds. Up to now, few efficient vaccines against E. mitis have been reported, whereas the recombinant subunit vaccines delivered by nanomaterials may elicit an encouraging outcome. Thus, in this study, we chose E. mitis 1a (Em1a) protein as the candidate antigen to generate Em1a preparations. The recombinant Em1a (rEm1a) protein was encapsulated with poly lactic-co-glycolic acid (PLGA) and chitosan (CS) nanospheres. The physical characterization of the rEm1a-PLGA and rEm1a-CS nanospheres was investigated, and the resulting nanospheres were proven to be nontoxic. The protective efficacy of rEm1a-PLGA and rEm1a-CS preparations was evaluated in E. mitis-challenged birds in comparison with two preparations containing rEm1a antigen emulsified in commercially available adjuvants. ELISA assay, flow cytometry analysis, and quantitative real-time PCR (qPCR) analysis indicated that vaccination with rEm1a-loaded nanospheres significantly upregulated the secretions of antibodies and cytokines and proportions of CD4+ and CD8+ T lymphocytes. Compared with the other three preparations, rEm1a-PLGA nanosphere was more effective in improving growth performance and inhibiting oocyst output in feces, indicating that the PLGA nanosphere was associated with optimal protection against E. mitis. Collectively, our results highlighted the advantages of nanovaccine in eliciting protective immunity and may provide a new perspective for developing effective vaccines against chicken coccidiosis.